Description and occurence of tuna and tuna-like larvae in Sulu Sea - Baguilat, Rachel B. (Iloilo, Philippines University of the Philippines in the Visayas, 1987)
A total of 284 tuna larvae was sorted from the ichthyoplankton samples collected on board the R/V Sardinella in the Sulu sea during the October-November 1982, February-March 1983. April and 84 and May 1984 cruises. Six genera and 5 species were identified. These are Thunnusalbacares (yellowfin), Katsuwonuspelamis (skipjack, Gymnosardaunicloro (dogtooth tuna), Acanthocybiumsolandri (wahoo), Auxisthazard (frigate tuna), four identified species of Auxis (bullet tuna) and one unidentified species of Euthynnus (eastern little tuna). The occurrence of G. unicolor and A. solandri larvae is recorded for the first time in the Philippines. During the October-November 1982 cruise, T. albacares was the most abundant while auxis species was predominant during the February-March 1983 cruise. In general, tuna larvae were found to be abundant during the February-March 1983 cruise and were concentrated southwest of the Sulu Sea. The period is characterized by low temperature (26.50 C = mean) in which tuna larvae are reported to abound. The distribution of larvae in relation to some physical and biological factors are discussed.
Thesis--(M.S. Fisheries-Fisheries Biology) --Faculty of Fisheries, Philippines:University of the Philippines in the Visayas, February 1987.
Keywords: Tuna